Neurobiology of Loneliness, Isolation, and Loss: Integrating Human and Animal Perspectives - Vitale, Erika M.; Smith, Adam S. (Frontiers in Behavioral Neuroscience, 2022)
In social species such as humans, non-human primates, and even many rodent species, social interaction and the maintenance of social bonds are necessary for mental and physical health and wellbeing. In humans, perceived isolation, or loneliness, is not only characterized by physical isolation from peers or loved ones, but also involves negative perceptions about social interactions and connectedness that reinforce the feelings of isolation and anxiety. As a complex behavioral state, it is no surprise that loneliness and isolation are associated with dysfunction within the ventral striatum and the limbic system – brain regions that regulate motivation and stress responsiveness, respectively. Accompanying these neural changes are physiological symptoms such as increased plasma and urinary cortisol levels and an increase in stress responsivity. Although studies using animal models are not perfectly analogous to the uniquely human state of loneliness, studies on the effects of social isolation in animals have observed similar physiological symptoms such as increased corticosterone, the rodent analogue to human cortisol, and also display altered motivation, increased stress responsiveness, and dysregulation of the mesocortical dopamine and limbic systems. This review will discuss behavioral and neuropsychological components of loneliness in humans, social isolation in rodent models, and the neurochemical regulators of these behavioral phenotypes with a neuroanatomical focus on the corticostriatal and limbic systems. We will also discuss social loss as a unique form of social isolation, and the consequences of bond disruption on stress-related behavior and neurophysiology.